Middle English romances : authoritative textx, sources and backgrounds, criticism (New York : W. W. Norton, 1994)
Middle English romances. Sources and backgrounds.
Keywords: English literature; English romances; Arthurian romances; English literature -- Middle English, 1100-1500 -- History and criticism; English literature -- Middle English, 1100-1500.; Arthurian romances -- History and criticism; Romances, English -- History and criticism; Civilization, Medieval, in literature; Arthurian